Optimization Of Physical Characterization Of Malaysian Clay For Ceramic Tile Production - Chin, Chee Lung (2018)
Clay is an important raw material in manufacturing of ceramic tiles. From economical point of view, local clays are important for demand of local ceramic tile industries. However, no comprehensive research work was carried out on Malaysia clays for application in ceramic tiles. The research work is aimed to provide scientific data on characterization of Malaysian clays from Ipoh (Perak), Kuala Rompin (Pahang) and Mersing (Johor) and their suitability for ceramic tile industry. The research covered characterization of study clays, effect of ceramic tile processing parameters on properties of studied clays and application in ceramic tiles. The clays were characterized by chemical composition, mineralogy, rheological analysis, physical, thermal and fired properties. Results showed that Ipoh clay is coarser in particle size (14.6 um) than Kuala Rompin (7.2 um) and Mersing clays (6.0 um). For rheological behaviour, sodium tripolyphosphate (STPP) is the most suitable deflocculant for the studied clays with CEC of 16 to 40 meq/100g and optimum deflocculant of 0.10 to 0.24% for manufacturing of ceramic tiles by wet milling process. For mineralogical analysis, kaolinite was present abundantly in Ipoh clay of about 78.7%, while Kuala Rompin and Mersing clays are containing high percentage of quartz (34.1% and 43.9%, respectively) and illite (39.1% and 30.7%, respectively). Mineralogy of clay is greatly affecting the fired properties of studied clays, where Kuala Rompin and Mersing clays shown higher densification (2.3 – 2.5 g/cm3), higher shrinkage (9.0 – 13.0%), lower water absorption (0.0 – 2.0%), higher CTE (8.1 – 8.4 x10-6 'C-1) and darker fired colour (L* of 60 - 70) than Ipoh clay at firing temperature of 1200 'C. For processing parameters, pressing pressure and firing temperature have greater impact to drying and fired properties, while both moisturizing and milling time have minor effect on both drying and fired properties of studied clays. Statistical design of mixture experiment proves that the clays are suitable to be used for production of ceramic tiles but its application is highly dependent to ceramic tile production practice by pressing pressure and firing temperature. For commercial floor tile production practice, studied clays have only fulfilled categories of BIIb and BIII ceramic tiles. For commercial porcelain tile production practice, studied clays have fulfilled almost all the ranges of ceramic tiles from BIa to BIII. The outcome of the research work shows that mineralogy and particle size of clay, pressing pressure and firing temperature have direct influenced on fired properties of studied clays and ceramic tiles body formulation.